Participatory development in rural India - Kuhn, Berthold (New Delhi : Radiant Publishers, 1998)
With reference to District Udaipur, Rajasthan.
Includes bibliographical references (p. 277-294) and index.
Keywords: Rural development -- India; Non-governmental organizations -- India; Rural development -- Government policy -- india; Agricultural assistance -- India